Ecosystem carbon stocks of mangroves across broad environmental gradients in West-Central Africa: Global and regional comparisons - Kauffman, J.B.; Bhomia, R.K. (Public Library of Science, 2017)
Globally, it is recognized that blue carbon ecosystems, especially mangroves, often sequester large quantities of carbon and are of interest for inclusion in climate change mitigation strategies. While 19% of the world’s mangroves are in Africa, they are among the least investigated of all blue carbon ecosystems. We quantified total ecosystem carbon stocks in 33 different mangrove stands along the Atlantic coast of West-Central Africa from Senegal to Southern Gabon spanning large gradients of latitude, soil properties, porewater salinity, and precipitation. Mangrove structure ranged from low and dense stands that were <1m in height and >35,000 trees ha-1 to tall and open stands >40m in height and <100 ha-1. Tremendous variation in ecosystem carbon (C) stocks was measured ranging from 154 to 1,484 Mg C ha-1. The mean total ecosystem carbon stock for all mangroves of West-Central Africa was 799 Mg C ha-1. Soils comprised an average of 86% of the total carbon stock. The greatest carbon stocks were found in the tall mangroves of Liberia and Gabon North with a mean >1,000 Mg C ha-1. The lowest carbon stocks were found in the low mangroves of the semiarid region of Senegal (463 Mg C ha-1) and in mangroves on coarse-textured soils in Gabon South (541 Mg C ha-1). At the scale of the entirety of West-Central Africa, total ecosystem carbon stocks were poorly correlated to aboveground ecosystem carbon pools, precipitation, latitude and soil salinity (r2 = ≤0.07 for all parameters). Based upon a sample of 158 sites from Africa, Asia and Latin America that were sampled in a similar manner to this study, the global mean of carbon stocks for mangroves is 885 Mg C ha-1. The ecosystem carbon stocks of mangroves for West-Central Africa are slightly lower than those of Latin America (940 Mg C ha-1) and Asia (1049 Mg C ha-1) but substantially higher than the default Intergovernmental Panel on Climate Change (IPCC) values for mangroves (511 Mg C ha-1). This study provides an improved estimation of default estimates (Tier 1 values) of mangroves for Asia, Latin America, and West Central Africa.